Lemon aromatherapy for chemotherapy-induced nausea and vomiting in breast cancer patients - Marta Ulina Simbolon; Sri Maryuni; Tubagus Erwin (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI), 2026)
Background: Chemotherapy-induced nausea and vomiting remain distressing adverse effects of breast cancer treatment and may compromise hydration, nutritional intake, quality of life, and treatment adherence. Lemon aromatherapy is a simple non-pharmacological intervention that may complement standard antiemetic care. Purpose: To evaluate changes in nausea and vomiting severity following lemon aromatherapy among breast cancer patients undergoing chemotherapy. Method: This pre-experimental study used a one-group pretest-posttest design. Twenty breast cancer patients receiving chemotherapy were recruited through purposive sampling. Nausea and vomiting severity was measured using a Numeric Rating Scale before and after inhaled lemon aromatherapy administered approximately two hours after chemotherapy for 5-10 minutes. Preintervention and postintervention scores were compared using the Wilcoxon signed-rank test. Results: The mean nausea and vomiting severity score decreased from 8.15 ± 1.50 before the intervention to 4.00 ± 0.97 afterward. The Wilcoxon signed-rank test showed a statistically significant change between the two assessments (p < 0.001). Conclusion: Nausea and vomiting severity was lower after lemon aromatherapy in this small pre-experimental sample. Lemon aromatherapy may be considered as an adjunct to standard antiemetic care, although controlled studies are needed to establish its independent effect.